ANALISIS PELAKSANAAN PROGRAM KESEHATAN KERJA POS UPAYA KESEHATAN KERJA NELAYAN DI WILAYAH KERJA PUSKESMAS SUKAKARYA KOTA SABANG - Andrian Andrian; Tri Niswati Utami; Achmad Rifai (Jurnal Kesehatan dan Keselamatan Kerja Universitas Halu Oleo, 2021)
The fishing community in the working area of Sukakarya Health Center often experiences various types of diseases due to occupational accidents while fishing. To solve the problem of fishermen's work accidents, the government provides a UKK Post. However, the implementation of the fishermen's UKK Pos work health program has not run optimally. The purpose of this study was to analyze the implementation of the occupational health program in the occupational health efforts of fishermen. The type of this study was a qualitative study with a descriptive approach which is carried out in the working area of Puskesmas Sukakarya, Kota Sabang. Informants of this study were 7 people. Determination of informants in this study using purposive sampling technique. Data analysis was carried out descriptively using the data analysis technique model of Miles and Huberman. The results showed that the implementation of promotional, preventive, curative and rehabilitative activities for the occupational health program at Pos UKK was not optimal because the activities were only carried out 4 times a year, limited funds/budget for organizing Pos UKK activities, there was no training for program managers and cadres. Supporting factors for the implementation of the Pos UKK occupational health program are the demographic location of Sabang City, the support of the village head, the low health of fishermen. The inhibiting factors for activities are the location of Pos UKK which was not permanent (often moved), the lack of budget, the absence of training on occupational health for program officials and cadres. The conclusion of this study is that the implementation of the occupational health program at the fishermen's UKK post is not optimal because of inhibiting factors. It is recommended that the Health Office of Sabang City collaborates across sectors (Marine Service) to make training and seminars on occupational health for the person in charge of the Puskesmas occupational health program and the cadres of Pos UKK in the Sabang City area